Thermodynamic and Spectral Studies of Inclusion Complexes of Substituted Indole Derivatives with b-Cyclodextrin - Panda, Sunakar; Krushna Tripathy, Jagat (Asian Journal of Chemistry, 2010)
Indole and its analogous are very good pharmacophores for designing several chemotherapeutic reagents which exhibit wide spectrum of antimicrobial activities. The poor solubility of these compounds in polar medium is one of the limiting factors for better bioaccessibility of these compounds. In this work, some arylidenamino-1,3,4-thiadiazino[6,5b]indoles have been synthesized in their pure form. In order to increase the solubility of these compounds in polar medium for better pharmacological activities, inclusion complexes of arylidenamino-1,3,4- thiadiazino[6,5b]indoles with b-cyclodextrin have been prepared and their spectral and thermodynamic properties have been studied.